Assessment of awareness of keratoconus and its relation to eye rubbing among Saudi Arabia population - Nuwayyir Abdullah Alqasimi; Lujain Hatim Aljohani; Renato Ambrósio; Renato Ambrósio; Renato Ambrósio; Renato Ambrósio; Renato Ambrósio; Bader Saad AlQahtani; Bader Saad AlQahtani; Nasser Saleh Al Haydar; Bdour Raja Alanazi; Danah Tariq Alfurayhan; et al. (Frontiers in Ophthalmology)
BackgroundKeratoconus (KC) is a bilateral, asymmetric, progressive thinning of the cornea that causes a decrease in optical quality due to induced myopia, irregular astigmatism, and higher order aberrations. KC affects 1.38 per 1,000 individuals globally, with a higher prevalence in Asian and Middle Eastern populations. Eye rubbing has been recognized as one of the leading risk factors for KC.ObjectivesThis study aimed to assess the knowledge and awareness about KC and its relation to eye rubbing among the population of the Kingdom of Saudi Arabia.MethodsA cross-sectional study was conducted in 2024 among people residing in different regions of Saudi Arabia. Data collection was carried out using an online questionnaire consisting of 21 questions, which were divided into two sections. Prior to administering the questionnaire, informed consent was obtained, and the confidentiality of the collected data was ensured.ResultsThis survey had a total of 2,059 respondents. The majority of the participants in the study were female, and their ages ranged from 18 to 30 years. Most of the participants held a university degree or higher. In total, 44% of respondents reported having allergic disorders, while 57.6% demonstrated a lack of knowledge regarding KC. The level of KC awareness was poor among Saudi residents, with 74.8% showing insufficient awareness. The group with acceptable awareness of KC was predominantly aged between 18 and 30 years and female, with a percentage of 30.4%.ConclusionThe study revealed that Saudi citizens are not knowledgeable about KC and the risks associated with eye rubbing. Additionally, the study identified several KC risk factors, including but not limited to eye rubbing, allergies, and family history. To alleviate the burden of KC in Saudi Arabia, it is imperative to enhance public health awareness and discourage the habit of eye rubbing.